Phytoplankton and Its Relationship to White Leg Shrimp (Litopenaeus vannamei) Culture Productivity in Alasbulu, Banyuwangi - Hasna Kamilia; Bambang Budi Sasmito; Endang Dewi Masithah (Journal of Experimental Life Science)
Shrimp culture is related to phytoplankton's existence as a primary producer and water quality. Aside from their function as natural feed, phytoplankton has a role in maintaining the stability of the pond ecosystem. It is indicated by the high abundance and diversity of phytoplankton, as well as suitable water quality to support the productivity of shrimp culture. This research aimed to determine the correlation between phytoplankton structure community, water quality parameters, and shrimp productivity. This research used a descriptive method. This research was conducted in shrimp culture intensive system Alasbulu Village, Wongsorejo District, Banyuwangi on February-March 2020. The parameters observed are diversity and abundance of phytoplankton, water quality parameters, and production performance in each pond. Based on the results, six phytoplankton classes were identified: Bacillariophyceae (10 genera), Cyanophyceae (8 genera), Chlorophyceae (5 genera), Dinophyceae (2 genera), Euglenophyceae (1 genus), and Cryptophyceae (1 genus). Chlorophyceae dominated both ponds, followed by Cyanophyceae. Diversity index values on ponds 1 and ponds 2 were 1.39 and 1.50, respectively. Productivity of both ponds were 1.8 kg.m-2 and 1.4 kg.m-2; FCR (Feed Convertion Ratio) 1.1 and 1.3; ADG (Average Daily Growth) 0.3 g.day-1 and 0.25 g.day-1. It can be concluded from this research that high density of Chlorophyceae in phytoplankton community is one of the main causes that supported shrimp cultivation.